Ragam asesmen autentik dalam mewujudkan pembelajaran PAI yang bermakna - Aufa Fatchia Rahma; Abdul Munip (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2026)
The learning of Islamic Religious Education (PAI) is currently still dominated by test-based assessments that do not fully reflect the application of values in real life. This study aims to examine the concept, types, and role of authentic assessment in realizing meaningful PAI learning. The method used is a literature study (library research) with data collection techniques in the form of documentation studies from journal articles, books, and relevant scientific publications from 2021–2026. The data were obtained from Google Scholar and SINTA, then analyzed using content analysis techniques. The results of the study show that authentic assessment in PAI emphasizes the contextual application of knowledge, attitudes, and skills. The most common forms include performance assessments, religious projects, and reflective portfolios. This approach helps increase student learning engagement and strengthens the internalization of Islamic values. In conclusion, authentic assessment is an assessment approach that is very relevant to supporting meaningful, contextual, and practical PAI learning.